Religion and the Country in the Perspective of Pancasila - Puguh Yuli Setiawan; Faisal Santiago (Budapest International Research and Critics University, 2022)
This article discusses religion and the country from the perspective of Pancasila. Religion and state law are often contested in the public sphere. Through a qualitative approach, using the normative juridical method accompanied by a descriptive analysis will formulate the relationship between religion and the country from the perspective of Pancasila. The results of the study found that the country, in the name of the constitution, manages the relationship between religion and belief in presenting legal pluralism in living a harmonious political life.